Inefetividade da constituição: a resposta da teoria inclusiva - Sousa, Jefferson de Jesus (2020)
The work seeks to understand the relationship of the Federal Constitution and the process (in a broad sense), aiming at the implementation of fundamental rights, especially second-dimensional fundamental rights. The theoretical option was the use of Professor Willis Santiago Guerra Filho's work, especially the Inclusive Theory (in the sense of legal epistemology) created and developed by him. We analyzed the hermeneutic framework, the concepts of Constitution and legal norms. Then, we identified that Constitution is not effective in many of its aspects, which is why we investigated the reasons that would be promoting this situation: In the doctrinal plan, we found that the Symbolic Constitutionalization" promoted by "Efficacy Charges Theory" is one of the factors that hinder the effective process, as it refers to na indefinite future the duty to enforce rights and neutralizes the political participation of those interested. On the institutional level, the prevalence of the Executive Branch over the Legislative Branch and Declaratory Action of Unconstitutionality by Default and the Writ of Injunction, associated with the lack of a Constitutional Court that promotes through the constitutional principle of Proportionality the implementation of the Constitution, complete the panorama that explains the ineffectiveness. The conclusion we have reached is that there is a deficit of democratic participation of the population in decisions concerning fundamental rights (even indirectly, by representation); therefore, to change of this framework, there must necessarily be an institutional reform through Constitutional Amendment that institutes a genuine Constitutional Court with representativeness and possibility of effective political control by the population